Preparation method of electrode
By heating and degassing and degassing during the kneading of the electrode slurry, the peeling problem during the electrode vacuum drying is solved, and the preparation yield and the bonding stability of the material are improved.
Patent Information
- Application Number
- CN202380066861.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-09-22
- Filing Date
- 2023-08-29
- Publication Date
- 2025-04-25
AI Technical Summary
During the vacuum drying of the electrode, peeling of the electrode material from the substrate is prone to occur, resulting in a decrease in the production yield.
By performing heating and degassing and degassing and stirring during mixing the slurry, the moisture in the electrode material is sufficiently removed, thereby preventing electrode peeling during vacuum drying.
The production yield of the electrode is effectively improved, the occurrence of electrode peeling is reduced, and the stable bond between the electrode material and the substrate is ensured.
Smart Images

Figure CN119895587A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a method for preparing an electrode, and in particular to a method for preparing an electrode suitable for a battery electrode. Background Art
[0002] As a power source installed on vehicles driven by electricity, etc., and a power source installed on electrical products such as personal computers and portable terminals, a secondary battery with higher output and high capacity can be achieved by using a lithium-ion secondary battery. Among these secondary batteries, lithium-ion secondary batteries are particularly light in weight, have high energy density, and are preferably used as high-output power sources for vehicles such as electric vehicles (EVs), plug-in hybrid vehicles (PHVs), and hybrid vehicles (HVs), and it is expected that demand will increase in the future.
[0003] In recent years, as a form of secondary battery, a battery in which a solid electrolyte in powdered, granular, or plate-shaped form is used instead of a liquid electrolyte (electrolyte) has emerged. This is also called a so-called all-solid-state battery. Various research and development efforts are being conducted on this all-solid-state battery for its practical application.
[0004] In addition, fuel cells that are supplied with hydrogen and oxygen as fuel from the outside and extract the energy generated when they react to produce water in the form of electricity are also expected to have high energy efficiency and be clean energy with only water as the exhaust.
[0005] The electrodes used in these batteries can usually be prepared by the following method: a conductive aid and a binder are mixed with an electrode active material to prepare a slurry, the slurry is applied to a substrate such as a current collector, and then vacuum dried to form a plate, and the obtained plate is pressed and then punched or cut into an electrode shape for processing.
[0006] Conventionally, as a kneading method for preparing the slurry, a degassing stirring method such as vacuum decompression, ultrasonic wave, centrifugal separation, etc. has been used (for example, refer to Patent Documents 1 and 2, etc.).
[0007] However, each of these defoaming and stirring methods has advantages and disadvantages. When developing a well-kneaded electrode material, no matter which method is used, its disadvantages may become an obstacle to obtaining an electrode material of desired quality.
[0008] On the other hand, in the newly proposed method using a rotation-revolution mixer, kneading and degassing can be performed efficiently and sufficiently compared with the above-mentioned degassing and stirring method, and an electrode material with good quality can be obtained.
[0009] Prior art documents
[0010] Patent Documents
[0011] Patent Document 1: Japanese Patent No. 5148036
[0012] Patent Document 2: Japanese Patent Application Publication No. 2019-216060 Summary of the invention
[0013] Problems to be solved by the present invention
[0014] As described above, although electrodes that could not be produced before can be produced by using a rotation-revolution mixer, so-called electrode peeling, in which the electrode material portion peels off from the substrate, may occur during the vacuum drying step of the slurry, thereby reducing the production yield.
[0015] Therefore, an object of the present invention is to provide a method for producing an electrode which can suppress the occurrence of such electrode peeling and improve the production yield.
[0016] Means of solving the problem
[0017] According to the preparation method of the electrode of this embodiment, the method includes: a process of mixing an electrode active material, a conductive aid and a binder to obtain a slurry; a process of coating the slurry on a substrate; and a process of vacuum drying the coated slurry, wherein the mixing is carried out by a heating stirring treatment and a degassing stirring treatment at a temperature of more than 150°C and less than 200°C.
[0018] In addition, according to other embodiments of the preparation method of the electrode, the method includes: a process of mixing an electrode active material, a conductive aid, a binder and a solid electrolyte to obtain a slurry; a process of coating the slurry on a substrate; and a process of vacuum drying the coated slurry, wherein the mixing is carried out by a heating stirring treatment and a degassing stirring treatment at a temperature of more than 150°C and less than 200°C.
[0019] Effects of the Invention
[0020] According to the method for producing an electrode disclosed in the present embodiment, it is possible to provide a method for producing an electrode that suppresses electrode peeling during vacuum drying during production and improves production yield. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 1 is a flowchart illustrating a method for producing an electrode according to the present embodiment. DETAILED DESCRIPTION
[0022] <Preliminary research items>
[0023] As described in the above problem, by using a rotation-revolution mixer, electrodes that could not be produced conventionally can be produced. However, electrode peeling occurs during vacuum drying of the electrodes, which reduces the production yield.
[0024] The applicants have conducted in-depth research on the reasons for the reduction in the yield rate of such preparation, and it is presumed that the water contained in the raw materials is not fully removed during the process of mixing the raw materials to obtain the slurry. In other words, it is believed that the water remaining in the raw materials may be volatilized when heated to about 150°C during vacuum drying, and the bonding force between the electrode material and the collector (substrate) is weakened, resulting in the so-called electrode peeling in which the electrode material peels off from the substrate.
[0025] Therefore, the present inventors have found that, in addition to stirring while heating at 150° C. or higher in the kneading step for obtaining slurry as a pre-stage of vacuum drying, degassing and stirring are performed, which can suppress electrode peeling during the subsequent vacuum drying, thereby completing the present invention.
[0026] <Implementation Method>
[0027] Hereinafter, the embodiments will be described in detail based on the examples and drawings. In all drawings for describing the embodiments, components having the same functions are represented by the same or related symbols, and their repeated descriptions are omitted.
[0028] [Electrode preparation method]
[0029] As described above, the method for preparing an electrode according to one embodiment of the present invention includes: kneading an electrode active material, a conductive additive, and a binder to obtain a slurry; coating the slurry on a substrate; and vacuum drying the coated slurry. Figure 1 Each process is described in detail.
[0030] [Step of Obtaining Slurry (S1)]
[0031] Before obtaining the slurry, various raw materials contained as electrode materials are prepared. As the raw materials prepared here, for example, electrode active materials, conductive additives, adhesives, etc. can be cited. In addition, components can be added and matched in addition within the scope of not hindering the effects and advantages brought as the effects of the present invention.
[0032] The various raw materials prepared are mixed and kneaded to form a slurry in a uniform state. Figure 1 -Step (S1)). The slurry obtained here is preferably in a fully defoamed state. In this embodiment, the slurry is heated and stirred ( Figure 1 - Heating and stirring step (S1-1)) and degassing and stirring treatment ( Figure 1-Deaeration and stirring step (S1-2)) This step is performed. In addition, the order of the heating and stirring treatment and the deaeration and stirring treatment is not limited, and they can be performed simultaneously. In the following description, the case where the deaeration and stirring treatment is performed after the heating and stirring treatment is described as an example.
[0033] The step (S1-1) is characterized in that stirring is performed while heating to a temperature capable of removing water contained in the electrode material. The heating temperature at this time is preferably 150° C. to 200° C., and more preferably 180° C. to 200° C., for the purpose of effectively removing water.
[0034] By suppressing the upper limit of the heating temperature to 200° C., the raw materials, especially the binder, can be prevented from being decomposed and deteriorated, and mixing can be performed without causing ignition in the solvent.
[0035] In addition, in step (S1-1), known stirring conditions can be applied without particular limitation. For example, a stirring bar can be used to stir and mix the raw materials. In this case, the rotation speed of the stirring bar is preferably 50rpm-200rpm, more preferably 100rpm-200rpm, and further preferably 150rpm-200rpm.
[0036] In operation (S1-2), for example, known deaeration stirring treatment methods such as vacuum decompression treatment, ultrasonic treatment, centrifugal separation treatment, rotation and revolution stirring treatment can be applied, wherein preferably rotation and revolution stirring treatment. As the processing conditions when applying the rotation and revolution stirring method, for example, the rotation speed in the rotation and revolution mixer is preferably 100rpm-1000rpm, more preferably 500rpm-750rpm. In addition, the revolution speed is preferably 200rpm-2000rpm, more preferably 1000rpm-1500rpm.
[0037] The temperature at this time may be less than 150° C. or may be carried out at room temperature (25° C.) The pressure may be normal pressure (1 atmosphere) or may be reduced pressure, for example, about 1.0 kPa to 0.50 kPa.
[0038] As described above, by using the heating stirring treatment and the deaeration stirring treatment to obtain the slurry, the raw materials are uniformly mixed, and the deaeration can be fully performed, and the moisture in the raw materials can also be fully removed. By removing the moisture at this stage, the occurrence of undesirable conditions such as electrode peeling can be suppressed in the vacuum drying process described later.
[0039] When the heating and stirring treatment and the degassing and stirring treatment are performed simultaneously, the above-described step (S1-2) may be performed in an environment heated to 150°C to 200°C.
[0040] [Raw materials for electrode materials]
[0041] The raw materials constituting the electrode material are described below. As the raw materials, an electrode active material, a conductive auxiliary agent, and a binder are generally used.
[0042] As the electrode active material, various known materials can be used without particular limitation. When forming the positive electrode, a positive electrode active material is used. When forming the negative electrode, a negative electrode active material is used.
[0043] Examples of the positive electrode active material include MnO 2 , LiCoO 2 , LiMn 2 O 4 , and LiNiO 2 .
[0044] On the other hand, examples of negative electrode active materials include Zn, Li, graphite, Si-based materials, Li4Ti5O 12 wait.
[0045] In addition, as the conductive aid, for example, carbon black such as acetylene black, carbon materials such as graphite and carbon nanotubes are preferably used, and any known conductive aid can be used without particular limitation.
[0046] Furthermore, examples of the binder include fluorine-based binders such as polyvinylidene fluoride (PVdF) and polytetrafluoroethylene (PTFE), and rubber-based binders such as styrene butadiene rubber (SBR), and any known binder can be used without particular limitation.
[0047] However, a solvent is required to disperse or dissolve the binder component, but when water is used as a solvent, the active material such as a halogen compound will be deactivated and the slurry will become acidic. If the active material is deactivated, the reversible capacitance may decrease. In addition, even if a stainless steel foil with excellent acid resistance is used, the passive film on the surface of the stainless steel foil will be destroyed when it is in contact with the acidic slurry containing the halogen compound.
[0048] Corrosion increases, so a good electrode cannot be obtained.
[0049] Based on such reasons, for the conversion active material, it is preferred to use a non-aqueous binder in which the binder component is dispersed or dissolved by an organic solvent. In addition, as the solvent used in the non-aqueous binder, N-methyl-2-pyrrolidone (NMP), dimethylformamide (DMF), dimethylacetamide (DMA), dimethyl sulfoxide (DMSO), esters, ketones, ethers, amines, etc. can be cited.
[0050] In addition, for non-aqueous adhesives, solvents for adjusting viscosity may also be used as required. As solvents for this purpose, for example, N-methylpyrrolidone (NMP), pyrrolidone, N-methylthiopyrrolidone, dimethylformamide (DMF), dimethylacetamide, hexamethylphosphoramide, cyclohexanone, methyl isobutyl ketone, methyl ethyl ketone, etc. may be cited, but are not particularly limited.
[0051] At this time, when the electrode active material, conductive aid and binder as the above raw materials are contained, the content ratio (mass %) of these materials based on mass is expressed as electrode active material: conductive aid: binder = x: y: z, preferably in the range of 50≤x≤95, 2.5≤y≤45, 2.5≤z≤45. Furthermore, these ratios are more preferably in the range of 65≤x≤95, 2.5≤y≤20, 2.5≤z≤15.
[0052] Moreover, in the process of kneading the above-mentioned raw materials to obtain a slurry, the above-mentioned components and the solvent are combined in the initial mixing so that the solid content ratio is about 30% or less, and after the above-mentioned heating and stirring step (S1-1), it is preferably adjusted so that the solid content ratio is greater than 30% and less than 70%, and more preferably adjusted so that it is greater than 40% and less than 50%.
[0053] By adjusting the solid content ratio of the slurry to the above range, it is possible to avoid the situation where the solid content ratio is too low and the slurry separates, or the solid content ratio is too high and the slurry solidifies, causing the film to rupture in the subsequent coating step (S2), and it is impossible to obtain a uniform film with the required area as an electrode.
[0054] [Step of applying slurry (S2)]
[0055] Next, in order to obtain a plate-shaped electrode, the slurry obtained in the above step (S1) is applied on a substrate ( Figure 1 - coating step (S2)).
[0056] In this step (S2), as long as the obtained slurry can be coated on the substrate in a manner to form a coating film of a desired thickness, a known coating method can be used without particular limitation. As the coating method, for example, extrusion coating, gravure coating, reverse roll coating, dip coating, coater coating, blade coating, screen printing, etc. can be cited.
[0057] The thickness of the slurry during the coating is, for example, preferably 10 μm to 150 μm, more preferably 10 μm to 100 μm, and further preferably 10 μm to 50 μm.
[0058] In addition, as a substrate for coating slurry, as long as it is a flat plate that can form a stable coating film, it can be used without special restrictions. On the surface of the substrate, a collector composed of a metal film or the like can be provided, and by coating the slurry on the collector, through a vacuum drying process as the next process, and subsequent pressing processes and punching, cutting, etc., an electrode can be directly formed, so it is preferred.
[0059] As the current collector, any known material can be used without particular limitation as long as it is an electron conductor that does not cause chemical changes in the battery.
[0060] As a positive electrode current collector, typically, a metal material with good electrical conductivity is preferred, for example, aluminum, nickel, titanium, stainless steel, copper, and metal materials such as materials (primer foil) to which carbon coating is applied respectively are well known. In the case of using a conversion active material, a current collector with a wide potential window is preferred, especially since a high capacity is obtained by charging and discharging in a wide voltage range. As a material for such a current collector, stainless steel (for example, stainless steel foil) is preferred. Stainless steel has ferrite, martensite, austenite, etc. according to its organizational structure, but is not particularly limited. The thickness of the positive electrode current collector is not particularly limited, but from the perspective of both the capacity density of the battery and the strength of the current collector, about 5μm-50μm is appropriate, and more preferably about 8μm-30μm.
[0061] In addition, as the raw material of the negative electrode collector, typically, a metal material with good electrical conductivity is preferred, for example, copper (e.g., copper foil) and an alloy mainly composed of copper can be used. The thickness of the negative electrode collector is not particularly limited, but from the perspective of both the capacity density of the battery and the strength of the collector, 5 μm-50 μm is appropriate, more preferably 8 μm-30 μm.
[0062] [Slurry vacuum drying step (S3)]
[0063] Next, the slurry applied to the current collector obtained in the above step (S2) is vacuum dried to obtain an electrode active material layer (coating film) ( Figure 1 - Vacuum drying step (S3)).
[0064] This step (S3) can be performed, for example, by reducing the pressure to 1.0 kPa or less and heating to 150°C or higher. The pressure at this time is preferably 1.0 kPa to 0.50 kPa, and the temperature is preferably 150°C to 170°C.
[0065] In the present embodiment, by performing the above-mentioned step ( S1 ), it is possible to suppress the occurrence of electrode peeling or the like in the step ( S3 ).
[0066] The above describes the characteristic part of the electrode preparation in the present embodiment, but as a subsequent process, after compression molding by a roller press or the like to form a predetermined thickness as required, it is processed into a predetermined width and length by punching and cutting, thereby obtaining a battery electrode. The electrode thus obtained can be combined with other components by a known method to form a battery.
[0067] <Improvement>
[0068] Above, the preparation method of the electrode has been described, but in the present embodiment, the electrode material can be used in a solid-state battery as described below. In the implementation of this improved example, except that the electrode material is different, the operation and applicable conditions involved in its preparation are the same as the preparation method of the electrode described above, so the repeated description thereof is omitted.
[0069] [Raw materials for electrode materials]
[0070] The raw materials of the electrode material in the improved example are described below. As the raw materials, electrode active materials, conductive aids, binders and solid electrolytes are generally used. The improved example is characterized in that a solid electrolyte is added to the raw materials described above. Moreover, the electrode material is suitable for use in a fully solid battery composed of a solid electrolyte layer arranged between a positive electrode layer and a negative electrode layer.
[0071] Here, a positive electrode active material is used when forming the positive electrode, and a negative electrode active material is used when forming the negative electrode. These materials can be used without particular limitation, and known materials can be used.
[0072] As the positive electrode active material used here, in addition to the active materials described above, as preferred materials, there can be mentioned conversion type (also called decomposition regeneration reaction type) or alloy reaction type active materials, for example, preferably CuCl2, FeF2, S, AgCl, FeCl3, NiCl2, CoCl2, FeCl2, Li2S, LiCl, LiF, AgF, Br2, LiBr, CoF3, CuF2, CuF, BiF3, CuCl2, NiF2, LiI, I2, CoF2, FeF3, MnF3, CrF3, CuS, Li2Se, Se, CuSe, Cu2O, CoS2, Cu2S, NiS, FeS2, Te, Li2Te, VF3, FeS, CoSe2, MnS2, MnCl2, Co3S4, FeSe, TiF3, MnS, etc. Among them, CuCl2, FeF2, and S are preferred.
[0073] In addition, as a conversion type active material, for example, equivalent to a halogenated transition metal (CuCl2, FeF2, FeCl3, etc.) and an alkali metal halide (LiCl, LiF, etc.), charging and discharging are performed by a chemical reaction accompanying the decomposition and generation between lithium and the metal compound. On the other hand, as an alloy reaction type active material, for example, equivalent to Si, SiO, Sn, SnCl2, etc., charging and discharging are performed by a reaction accompanying the formation of a Li alloy phase.
[0074] These positive electrode active materials are contained in the form of particles, and the average particle size (D50) thereof based on a laser diffraction scattering method is preferably about 0.1 μm to 20 μm, and more preferably about 0.4 μm to 10 μm.
[0075] In addition, as the negative electrode active material used here, for example, conversion type, alloy reaction type, dissolution reaction type active materials of Si, Li, Sn, Mg, Al, etc. can be cited. Among them, from the perspective of the high or low energy density per unit weight or per unit volume, Si, Li, Mg, and Al active materials are preferred.
[0076] In addition, the dissolution reaction type active material corresponds to, for example, metal Li and metal Na, and charging and discharging are performed with the dissolution and precipitation of these metal phases.
[0077] As Si-based negative electrode active materials, there can be cited Si, a mixture of Si and SiO2 in which the Si to O ratio is 1:a (here, 0.05<a<1.95), a mixture of Si and SiC in which the Si to C ratio is 1:b (here, 0<b<1), a mixture of Si and Si3N4 in which the Si to N ratio is 1:C (here, 0<C<4 / 3), etc.
[0078] In addition, as other examples of Si-based negative electrode active materials, alloy materials composed of Si and elements other than Si can be cited. As elements other than Si mentioned here, for example, Fe, Co, Sb, Bi, Pb, Ni, Cu, Zn, Ge, In, Sn, Ti, etc. can be cited.
[0079] Examples of Sn-based negative electrode active materials include Sn, Sn oxides, Sn nitrides, Sn-containing alloys, and solid solutions thereof, etc. Some of the Sn atoms contained in these materials may be substituted with one or more elements other than Sn.
[0080] Examples of Sn oxides include tin oxide (SnO d(0<d<2)), tin dioxide (SnO2), etc. Examples of Sn-containing alloys include Ni-Sn alloys, Mg-Sn alloys, Fe-Sn alloys, Cu-Sn alloys, Ti-Sn alloys, etc. Examples of Sn compounds include SnSiO3, Ni2Sn4, Mg2Sn, etc.
[0081] Examples of the Li-based negative electrode active material include Li, In-Li alloy, Al-Li alloy, Mg-Li alloy, Zn-Li alloy, Sn-Li alloy, and Sb-Li alloy.
[0082] Examples of the Mg-based negative electrode active material include Mg, Ni-Mg alloy, Sn-Mg alloy, Fe-Mg alloy, Cu-Mg alloy, and Ti-Mg alloy.
[0083] Examples of the Al-based negative electrode active material include Al, Ni—Al alloy, Sn—Al alloy, Fe—Al alloy, Cu—Al alloy, and Ti—Al alloy.
[0084] These negative electrode active materials are contained in the form of particles, and the average particle size (D50) thereof measured by a laser diffraction scattering method is, for example, appropriately about 1 μm to 20 μm, and particularly preferably about 2 μm to 10 μm.
[0085] Examples of the solid electrolyte that can be used here include various oxide-based solid electrolytes and sulfide-based solid electrolytes.
[0086] As the oxide-based solid electrolyte, preferred substances include crystalline oxides having a NASICON structure, a garnet structure, or a perovskite structure. For example, a solid electrolyte having the general formula Li x AO y (herein, A is B, C, Al, Si, P, S, Ti, Zr, Nb, Mo, Ta or W, and x and y are positive numbers). Specific examples include Li3BO3, LiBO2, Li2CO3, LiAlO2, Li4SiO4, Li2SiO3, Li3PO4, Li2SO4, Li2TiO3, Li4Ti5O 12 , Li2Ti2O5, Li2ZrO3, LiNbO3, Li2MoO4, Li2WO4, etc. In addition, preferred examples can also be given for glasses or glass ceramics that do not have a specific crystal structure such as Li2O-B2O3-P2O5 system, Li2O-SiO2 system, Li2O-B2O3 system, Li2O-B2O3-ZnO system, etc.
[0087] In particular, from the viewpoint of having high ion conductivity, it is preferred to use a sulfide-based solid electrolyte, for example, glasses or glass ceramics such as Li2S-SiS2, Li2S-P2S3, Li2S-P2S5, Li2S-GeS2, Li2S-B2S3, Li3PO4-P2S5, and Li4SiO4-Li2S-SiS2 can be cited.
[0088] From the viewpoint of achieving higher ion conductivity, it is preferred to use a solid solution based on Li2S composed of Li2S and lithium halide (e.g., LiCl, LiBr, LiI). Preferred substances include LiBr-Li2S-P2S5, LiI-Li2S-P2S5, LiBr-LiI-Li2S-P2S5, etc.
[0089] These solid electrolytes are used in the form of particles, and their average particle size (D50) based on a laser diffraction scattering method is, for example, preferably 0.1 μm to 10 μm, and more preferably 0.4 μm to 5 μm.
[0090] Example
[0091] Hereinafter, this embodiment will be described in more detail with reference to examples.
[0092] Examples 1-9, Comparative Example 1
[0093] First, prepare copper chloride (CuCl2) as a positive electrode active material, acetylene black as a conductive additive, polyvinylidene fluoride (PVdF) as a binder, and Li2O-Al2O3-SiO2-P2O5-TiO2 as a solid electrolyte.
[0094] Using N-methyl-2-pyrrolidone (NMP) as a solvent, the raw materials were kneaded according to the combination of the above raw materials recorded in Table 1 to obtain a slurry. The kneading was first heated at 180°C, and dehydrated and stirred for 2 hours with the rotation speed of the stirrer set to 50 rpm. Then, the slurry for coating was obtained by degassing and stirring for 5 minutes at normal pressure, a rotation speed of 500 rpm, and a revolution speed of 1000 rpm using a rotation and revolution mixer (Rentaro Awado (manufactured by THINKY Co., Ltd., trade name)). The solid content ratio of the obtained coating slurry after formation is shown in Table 1. In addition, in Comparative Example 1, during kneading, no heating and stirring treatment was performed, and a degassing and stirring treatment was immediately performed to obtain a slurry.
[0095] The slurry was applied to a copper or stainless steel substrate using a bar coater to a thickness of 150 μm, and vacuum dried at 60° C. or 80° C. for 12 hours to form a coating film. The obtained coating film was pressed to a thickness of 70 μm, punched, and vacuum dried at 150° C. to obtain a positive electrode.
[0096] Table 1
[0097]
[0098] At this time, in Examples 1-9 in which a heating and stirring step was performed in the process of obtaining the slurry, no electrode peeling occurred during vacuum drying. On the other hand, in Comparative Example 1, when the raw materials were kneaded in a rotation-revolution mixer without the heating and stirring step, electrode peeling occurred during vacuum drying.
[0099] As mentioned above, although this invention was specifically described by embodiment, this invention is not limited to these embodiment and is interpreted, It is a matter of course that various changes can be made within the range which does not deviate from the summary.
Claims
1. A method for preparing an electrode, the method comprising: A process of mixing an electrode active material, a conductive aid and a binder to obtain a slurry; The process of coating the slurry on a substrate; as well as The step of vacuum drying the applied slurry, The kneading is performed by heating and stirring at a temperature of 150° C. to 200° C. and degassing and stirring.
2. The method for preparing an electrode according to claim 1, wherein: The heating and stirring treatment is performed at a temperature of 180° C. or higher and 200° C. or lower.
3. The method for preparing an electrode according to claim 1, wherein: Regarding the electrode active material, the conductive auxiliary agent and the binder, When the content ratio based on mass is expressed as electrode active material:conductive aid:binder=x:y:z, the content ratio (mass %) is in the range of 50≤x≤95, 2.5≤y≤45, and 2.5≤z≤45.
4. A method for preparing an electrode, the method comprising: A process of mixing an electrode active material, a conductive aid, a binder and a solid electrolyte to obtain a slurry; The process of coating the slurry on a substrate; as well as The step of vacuum drying the applied slurry, The kneading is performed by heating and stirring at a temperature of 150° C. to 200° C. and degassing and stirring.
5. The method for preparing an electrode according to claim 4, wherein: The heating and stirring treatment is performed at a temperature of 180° C. or higher and 200° C. or lower.
6. The method for preparing an electrode according to claim 4, wherein: Regarding the electrode active material, the conductive auxiliary agent, the binder and the solid electrolyte, The content ratio based on mass is electrode active material: conductive additive: When binder:solid electrolyte=x:y:z:v is expressed, the content ratio (mass %) thereof is in the range of 50≤x≤92.5, 2.5≤y≤45, 2.5≤z≤45, and 2.5≤v≤45.
7. The method for preparing an electrode according to claim 4, wherein: The electrode active material is a positive electrode active material.
8. The electrode preparation method according to claim 7, wherein: The electrode active material is a conversion type active material or an alloy reaction type active material.
9. The method for preparing an electrode according to claim 8, wherein: The electrode active material is composed of a material selected from CuCl2, FeF2 and S.
10. The method for preparing an electrode according to claim 9, wherein: This method uses stainless steel as the current collector material.
11. The method for preparing an electrode according to claim 9, wherein: This method uses a non-aqueous binder as the binder.
Citation Information
Patent Citations
Suiryokubuhinnotaishoku taimamoseiotakameru hoho
JP1976048036A
Production method of coating liquid for forming fine porous layer of gas diffusion electrode
JP2019216060A